Interpolation method for quaternionic-Bezier curves - Zube, Severinas (Lietuvos matematikos rinkinys, 2018)
We study rational quaternionic-Bézier curves in three dimensional space. We construct the quadratic quaternionic-Bézier curve which interpolates five points, or three points and two tangent vectors.
Keywords: quaternionic-Bézier curve; interpolation